2020
DOI: 10.1101/2020.08.06.236596
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The longitudinal stability of fMRI activation during reward processing in adolescents and young adults

Abstract: BackgroundThe use of functional neuroimaging has been an extremely fruitful avenue for investigating the neural basis of human reward function. This approach has included identification of potential neurobiological mechanisms of psychiatric disease and examination of environmental, experiential, and biological factors that may contribute to disease risk via effects on the reward system. However, a central and largely unexamined assumption of much of this research is that neural reward function is an individual… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 110 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…For example, an activation elicited by emotional faces relative to baseline shows higher ICCs than activation of emotional faces relative to neutral faces (which is totally unreliable in the ABCD data). Similarly, Baranger et al (2021) recently demonstrated using a number-guessing reward task that reward activation contrasted with baseline had greater reliability than reward contrasted directly with loss. However, contrasts with baseline lack specificity because they may include activation elicited by emotional content as well as nonspecific activation that can be attributed to any outcome regardless of semantic content, and even activation that is common to visual stimuli in general, resulting in poor discriminant validity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, an activation elicited by emotional faces relative to baseline shows higher ICCs than activation of emotional faces relative to neutral faces (which is totally unreliable in the ABCD data). Similarly, Baranger et al (2021) recently demonstrated using a number-guessing reward task that reward activation contrasted with baseline had greater reliability than reward contrasted directly with loss. However, contrasts with baseline lack specificity because they may include activation elicited by emotional content as well as nonspecific activation that can be attributed to any outcome regardless of semantic content, and even activation that is common to visual stimuli in general, resulting in poor discriminant validity.…”
Section: Discussionmentioning
confidence: 88%
“…For example, an activation elicited by emotional faces relative to baseline shows higher ICCs than activation of emotional faces relative to neutral faces (which is totally unreliable in the ABCD data). Similarly, Baranger et al (2021) recently demonstrated using a number-guessing reward task that reward activation contrasted with baseline had greater reliability than reward contrasted directly with loss.…”
Section: Task Design and Specific Contrastsmentioning
confidence: 88%
“…Beyond behavioral measures, the Reliability Paradox is also apparent in neuroscience-a recent meta-analysis of 90 fMRI experiments showed an average task-based BOLD response 𝜌 ≈ .4 across different brain regions and tasks (16). Resting state, task-based, and regional activation/connectivity measures show comparably low reliability (24)(25)(26), suggesting that-like behavioral tasks-many neural measures cannot be used for clinical decision-making.…”
Section: The Reliability Paradox and Brain-behavior Relationshipsmentioning
confidence: 99%
“…The following a priori reward‐related regions were selected: caudate, putamen, AI, NAcc, and vmPFC. Reward‐related neural activation has adequate stability over a 1‐ to 2‐year period (Baranger et al., 2021), supporting the use of neural activation to reward as a trait‐level predictor in short‐term longitudinal analysis. Finally, we explored the association between peer connectedness during the pandemic and pre‐existing neural activation to positive peer feedback, based on work showing a link between neural activation to social feedback and daily peer connectedness (Silk et al., under review).…”
mentioning
confidence: 95%